The Relationship of Addictive Attitudes, Propensity to Search for Thrills and Psychological Defenses of Personality in Drug-addicted Convicts - I.S. Ganishina; M.I. Maryin; V.V. Azhimov (Психология и право)
The relevance of the chosen topic is due to the importance of studying addictive attitudes, a tendency to search for thrills and psychological defenses of personality in drug-addicted convicts, which are taken into account when compiling psychological characteristics in places of deprivation of liberty, and, further, are evaluated in dynamics when serving a criminal sentence by convicts. The empirical study was conducted on the basis of the FKU IK-1 of the Federal Penitentiary Service of Russia for the Udmurt Republic. 114 convicts with drug addiction and 108 convicts without drug addiction took part in it. The revealed differences characterize the sample of drug-addicted convicts as persons who still have a high need and willingness to use narcotic substances, even in conditions of serving a criminal sentence. Significant interrelations between additive attitudes, thrill seeking and psychological defenses indicate the existing risk of destructive behavior of convicts. The study of the stated indicators will allow penitentiary psychologists to make an adequate forecast of the behavior of drug-addicted convicts in a correctional institution.The prospects of the problem under study are the development of a psychocorrection program taking into account the identified indicators and its use in the professional activities of penitentiary psychologists.